Efficacy and safety of Saccharomyces boulardii in amebiasis-associated diarrhea in children - Savaş-Erdeve, Senay; Gökay, Songül; Dallar, Yıldız (The Turkish Journal of Pediatrics, 2009)
The efficacy and safety of adding Saccharomyces boulardii to antibiotic treatment for amebiasis-associated acute diarrhea in children were assessed in this study. Forty-five children in Group I received only metronidazole per oral for 10 days while 40 patients in Group II received S. boulardii in addition to the same medication. The major outcomes investigated were duration of acute and bloody diarrhea, frequency and consistency of stools, resolution time of the symptoms, and the tolerance and side effects of the treatment regimens. The median duration of acute diarrhea was 5 (1-10) days in Group I and 4.5 (1-10) days in Group II (p=0.965). The median number of stools on follow-up and duration of bloody diarrhea, fever, abdominal pain and vomiting were similar in the two groups. S. boulardii was well tolerated by the children and no side effects were recorded. Addition of S. boulardii to antibiotic treatment of amebiasis-associated acute diarrhea in children does not seem to be more effective than metronidazole treatment alone.